Everybody's got something [large type] - Roberts, Robin, 1960- (Grand Central Publishing Large Print, 2014)
The beloved Good Morning America anchor shares the incredible journey that's been her life so far and the lessons she learned along the way as she battled breast cancer and a rare blood disorder and dealt with the death of her mother.